2020
DOI: 10.1126/sciadv.aaz4157
|View full text |Cite
|
Sign up to set email alerts
|

Tumor cell–organized fibronectin maintenance of a dormant breast cancer population

Abstract: Tumors can undergo long periods of dormancy, with cancer cells entering a largely quiescent, nonproliferative state before reactivation and outgrowth. To understand the role of the extracellular matrix (ECM) in regulating tumor dormancy, we created an in vitro cell culture system with carefully controlled ECM substrates to observe entrance into and exit from dormancy with live imaging. We saw that cell populations capable of surviving entrance into long-term dormancy were heterogeneous, containing quiescent, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(91 citation statements)
references
References 85 publications
5
86
0
Order By: Relevance
“…Similarly, our findings have detected strong vinculin-supported lateral interactions at the cell-cell level inducing the formation of stable cell aggregates in Sox2 overexpressing cells. Furthermore, the presence of dormant tumor cells has been associated with increased metastatic risk and poor prognosis, and these cells appear to display an adherent phenotype and increased glycoproteins and proteoglycans, including fibronectin deposition, under cellular stress [59]. It will be noteworthy to further understand the mechanism by which alterations in integrin expression or syndecan levels may affect binding to fibronectin and the potential consequences in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, our findings have detected strong vinculin-supported lateral interactions at the cell-cell level inducing the formation of stable cell aggregates in Sox2 overexpressing cells. Furthermore, the presence of dormant tumor cells has been associated with increased metastatic risk and poor prognosis, and these cells appear to display an adherent phenotype and increased glycoproteins and proteoglycans, including fibronectin deposition, under cellular stress [59]. It will be noteworthy to further understand the mechanism by which alterations in integrin expression or syndecan levels may affect binding to fibronectin and the potential consequences in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies suggest that elevated legumain expression leads to worse outcomes in glioblastoma, breast, colorectal and ovarian cancer patients [293][294][295][296] and legumain is suggested as a potential target for tumour therapy [62,297,298]. In fact, in paper IV we demonstrate FN degradation by legumain and tumour cells use degradation and remodelling of ECM by proteases for tumour metastasis as mentioned above [299,300]. In paper III we show an inverse relationship between legumain and VDR both in vitro and in vivo, and high VDR expression is a positive prognostic factor in cancer [301].…”
Section: Cancermentioning
confidence: 58%
“…Tet2, in turn, activates the cell cycle suppressors p21-p27 and induces integrin β3 downregulation, respectively, promoting and preserving dormancy (183). Moreover, a recent deep single cell analysis revealed a high phenotypic heterogeneity in dormant cancer cells, encompassing pools of quiescent, senescent, and actively proliferating cells (184). The characterization of cells entering long-term dormancy demonstrated that these cells adhere stably to a stiff matrix through integrin α5β1 and rho-associated kinase (ROCK)-mediated cell tension.…”
Section: The Ecm: a Biochemical And Biophysical Niche For Cancer Cellsmentioning
confidence: 99%
“…The characterization of cells entering long-term dormancy demonstrated that these cells adhere stably to a stiff matrix through integrin α5β1 and rho-associated kinase (ROCK)-mediated cell tension. Moreover, the capability to exit from dormancy appears strictly connected to the ability to trigger MMP-mediated FN1 degradation (184).…”
Section: The Ecm: a Biochemical And Biophysical Niche For Cancer Cellsmentioning
confidence: 99%